Meningkatkan Motivasi Belajar Peserta Didik Melalui Media Interaktif Dalam Pembelajaran Matematika Siswa Kelas II di SD Negeri 22 Palu - Muhammad Nazimuddin Al Kamil; Rahmita; Rangga Putra Boroallo (JURNAL DIKDAS, 2024)
This study aims to enhance the mathematics learning motivation of second-grade students at SD Negeri 22 Palu through the implementation of interactive media. The research utilized Classroom Action Research (CAR) conducted in two cycles, with each cycle comprising planning, implementation, observation, and reflection stages. The subjects were 30 second-grade students. Data were collected through observation and interviews, then analyzed descriptively both qualitatively and quantitatively. The success indicator was set if at least 80% of students demonstrated high learning motivation. The results showed a significant increase in students' learning motivation across all indicators, including active engagement, desire and willingness to learn, response to feedback, persistence in completing tasks, and enthusiasm for the subject matter. The average learning motivation increased from 47% in the pre-cycle, to 71% in the first cycle, and reached 91% in the second cycle. These findings demonstrate that the use of innovative and engaging interactive media can effectively improve students’ motivation in learning mathematics. This study recommends the broader use of interactive media in the learning process and encourages schools to provide adequate support and facilities.